2009
DOI: 10.1345/aph.1l242
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Appropriate Drug Use Through the Application of the Spanish Drug-Related Problem Classification System in the Primary Care Setting

Abstract: The current Spanish DRP classification system is a useful tool to systematically detect and document DRPs in daily general practice. In addition, the interventions addressed by pharmacists to GPs and patients resolved most of the detected DRPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 26 publications
0
23
1
2
Order By: Relevance
“…In comparison to our finding of seven unmet indicators or potential DRPs per patient, studies outside Australia have reported a range of 0.58–8.6 DRPs per patient, [8,27–29,34–36,57–59] and Australian studies have reported a range of 2.5–9.7 DRPs per patient [9–12,30,32,60,61] . The majority of these studies were performed in the community, with two performed in hospitals, [27,57] one study on discharge from hospital [10] and one study in residential care [11] .…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In comparison to our finding of seven unmet indicators or potential DRPs per patient, studies outside Australia have reported a range of 0.58–8.6 DRPs per patient, [8,27–29,34–36,57–59] and Australian studies have reported a range of 2.5–9.7 DRPs per patient [9–12,30,32,60,61] . The majority of these studies were performed in the community, with two performed in hospitals, [27,57] one study on discharge from hospital [10] and one study in residential care [11] .…”
Section: Discussioncontrasting
confidence: 70%
“…However, because there is no accepted standard tool for classification and documentation of DRPs, [59] most of these 18 studies used different DRP classification systems, with some using a combination of systems. Eleven studies used nine different DRP classification systems, [10,12,30,32,35,36,57,60,61] four studies modified existing DRP classification systems [8,11,27,29,34,36,58] and three studies used systems based on or including national prescribing guidelines [8,9,28] . Reviews of DRP classification systems have stated that none met all criteria for an optimal system, [62] and that it was not possible to compare total numbers of documented problems between systems [63] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los estudios observacionales en este grupo de pacientes frágiles muestran (tabla 4-3) una importante proporción de tratamientos con interacciones potencialmente graves 53,54 , de medicación inadecuada (especialmente psicofármacos) [55][56][57][58][59][60][61] , desconocimiento de aspectos esenciales de la posología o el tratamiento 51 , ausencia de tratamientos efectivos 62-64 y un elevado volumen de problemas relacionados con medicamentos y reacciones adversas [64][65][66][67] . En otro terreno, también resulta alarmante los porcentajes de automedicación en estos pacientes que elevan las posibilidades de interacciones.…”
Section: Ancianos Crónicos Y Polimedicadosunclassified
“…1,[10][11][12][13][15][16][17][18] The result has been the development of classification systems dissimilar to one another in terms of category size, type, and content, with lack of adoption of a universally accepted classification system, and consequent difficulty in comparing numbers and types of DRPs and their causes between studies. 1,9,16,17,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] For example, categories identified as causes of DRPs have varied in number from six 39 to 37, 40 and the number of DRP cause subcategories have varied from nine 9 to 48. 12 As stated, there has also been variability in the definition of DRPs, and in categories identified as causes of DRPs or as DRPs themselves, 17,19,31,33,34,36,37,41,42 with some classification systems containing categories identified only as DRPs, …”
Section: Introductionmentioning
confidence: 99%